Activated thrombin‐activatable fibrinolysis inhibitor (TAFIa) attenuates fibrin‐dependent plasmin generation on thrombin‐activated platelets. (31st August 2020) - Ni, Ran; Neves, Miguel A. D.; Wu, Chengliang; Cerroni, Samantha E.; Flick, Matthew J.; Ni, Heyu; Weitz, Jeffrey I.; Gross, Peter L.; Kim, Paul Y.
Abstract: Background: Thrombin‐activated platelets can promote fibrinolysis by binding plasminogen in a fibrinogen‐dependent manner and enhancing its activation by tissue‐type plasminogen activator (t‐PA). Whether t‐PA also binds to activated platelets and the mechanism for regulation of platelet‐dependent fibrinolysis remain unknown. Objectives: Determine the mechanism of plasminogen and t‐PA binding on thrombin‐activated platelets and its regulation by activated thrombin‐activatable fibrinolysis inhibitor (TAFIa). Methods: Plasminogen and t‐PA binding with or without TAFIa treatment was quantified using flow cytometry. Plasmin generation on platelets was quantified using a plasmin‐specific substrate. Mass spectrometry analyses identified fibrinogen as a potential target of TAFIa. Thrombus formation was studied in mice lacking fibrinogen (Fg ‐/‐ ) using intravital microscopy. Results: Plasminogen and t‐PA bind to platelets activated by thrombin but not by other agonists, including protease‐activated receptor agonists (PAR‐AP). Plasminogen binds via its kringle domains because ε‐aminocaproic acid eliminates binding, whereas t‐PA binds via its finger and kringle domains. Plasminogen binding is fibrinogen‐dependent because it is abolished on (a) Fg ‐/‐ platelets, and (b) thrombi in Fg ‐/‐ mice. Binding requires thrombin‐mediated fibrinogen modification because addition of batroxobin to PAR‐AP activated platelets has no effect on plasminogen binding but induces t‐PA binding. TAFIa reduces plasminogen and t‐PA binding to thrombin‐activated platelets and attenuates plasmin generation in a concentration‐dependent manner. Mass spectrometry identified K556 on the fibrinogen alpha‐chain as a potential thrombin cleavage site that generates a TAFIa sensitive C‐terminal lysine residue. Conclusion: These findings provide novel mechanistic insights into how platelets activated by thrombin at sites of vascular injury can influence fibrinolysis.